Digital Inclusive Finance and Rural Household Income: An Empirical Study - Wang, Yijing (Simen Owen Academic Proceedings Series, 2025)
Based on panel data from 31 provinces, autonomous regions, and municipalities in China between 2011 and 2020, this study employs a fixed-effects model to investigate the impact mechanisms and outcomes of digital inclusive finance on rural household income. The empirical results indicate that, overall, the expansion of digital inclusive finance has significantly contributed to income growth among rural residents. A more detailed examination of sub-dimensions reveals that the breadth of coverage exerts a particularly strong positive influence, while the effects of usage depth and the level of digitalization are relatively less pronounced. This suggests that ensuring widespread access to digital financial services is more critical for enhancing rural income than merely deepening the intensity or sophistication of usage. Further analysis of regional differences demonstrates that the western region of China has experienced more substantial benefits from the development of digital inclusive finance compared to other regions. This finding underscores the importance of considering regional heterogeneity when formulating policies aimed at promoting digital financial inclusion and rural economic development. Moreover, the study highlights a clear "threshold effect" associated with rural digital infrastructure. Specifically, when digital infrastructure reaches a certain level, the marginal promoting effect of digital inclusive finance on rural income growth diminishes. This phenomenon suggests that while initial investments in digital infrastructure can substantially boost the effectiveness of digital financial services, the incremental benefits may taper off once a baseline level of infrastructure maturity is achieved. These findings provide both empirical evidence and a theoretical foundation for improving the rural financial service system, optimizing strategies for digital inclusive finance, and enhancing the income potential of rural households. The results carry particular significance for the implementation of rural revitalization strategies and the advancement of urban-rural integration, offering valuable guidance for policymakers seeking to leverage digital finance as a tool for inclusive economic growth.